Population growth and urbanization what does the future hold? - Cho, Lee-Jay; Bauer, John G. ([1987])
Projections of urbanization levels and urban populations merely extrapolate recent trends. These trends are sometimes subject to substantial changes as economic conditions change.
Trends in urbanization, urban population growth, and city size -- Projected trends -- Evaluation of the projections -- City population projections -- Determinants of urbanization -- Sensitivity of urban trends to determinants.
Photocopy.
Source : Fuchs, R.J., Jones, G.W. and Pernia, E.M. (eds.) Urbanization and urban policies in Pacific Asia. Boulder : Westview Press. 1987.
Keywords: Urbanization -- Asia; Urban policy -- Asia; Population growth